Effets de l’extrait au méthanol aqueux de Thymus vulgaris L. (Thym) récolté à Naama (Algérie) sur les germes spécifiques du yaourt –Caractérisation des composés bioactifs de la plante-Essai de fabrication d’un lait fermenté. - DEHIMECHE, Nafissa (My University, 2017)
This study contributes to the knowledge of the composition of bioactive constituents ofThymus vulgaris L. harvested in Mechria region of Naama in the south of Algeria and their antimicrobial effects on the specific germs of yoghurt (Streptococcus thermophilus and Lactobacillus bulgaricus).The study also aims to determine the effect of the incorporation of hydromethanol extract of thyme at different doses (0, 2, 4, 6 and 8%) on the quality and stability of a fermented milk (yoghurt) for 21 days cold storage at 4 ° C.The extraction of the bioactive compounds from the plant was realised by cold maceration with aqueous methanol. After evaporation of the solvent in vacuo, the extracts obtained are prepared in a proportion of 0, 20, 40, 60, 80 and 100%. In order to characterize the experimental extract of Thymusvulgaris L., qualitative and quantitative analyzes were performed (tube test, total polyphenol assay, flavonoid assay, TLC and HPLC).Concerning the antimicrobial activity of thyme various methods and measurements were tested, such as growth rate, inhibition diameter, Minimum Inhibitory Concentration and Minimum Bactericidal Concentration.Finally, measurements made on yoghurt with added thyme extract were carried out on (pH, acidity, viscosity, tackiness, cohesiveness, taste, odor, Color and freshness). Apparently, the Thymus vulgaris L. object of the study is rich in major bioactive compounds including tannins, alkaloids, polyphenols and flavonoids.The total polyphenol and flavonoid compounds in the hydromethanol extract of the plant were estimated at 39.83 μgEQ / mg and 20.2 μgEAG / mg, respectively. The quercetin, flavonols 5,6,7 tri OH, flavones 5 OH and 4 OH; ISO flavones, flavonols 3-OH and dihydroflavonols were the principal flavonoid compounds identified in the studied plant. These bioactive compounds demonstrated a bactericidal effect on the two lactic strains (Streptococcus thermophilus and Lactobacillus bulgaricus) at 80% of hydromethanolic extract of Thymus vulgaris L. It would appear that the quality (physicochemical, microbiological and organoleptic) was significantly altered (P <0.01) with the increase in concentrations of thymus extract (0, 2, 4, 6 and 8%) respectively in the fermented milks.Nevertheless, the products prepared at 2 and 4% of extract were very appreciated by the consumers than control yogurt.
Keywords: Thymus vulgaris L.; extract; aqueous methanol; Streptococcus thermophilugsm; Lactobacillus bularicus; bactericide; yogurt; fermented ilk.